ANALISIS PENGUKURAN KINERJA PEMERINTAH DAERAH DENGAN MENGGUNAKAN PRINSIP VALUE FOR MONEY (STUDY KASUS KABUPATEN SUMENEP TAHUN 2010-2013) - CAHYA FERISKA SARI, NINDY Feriska (Jurnal Akuntansi AKUNESA, 2014)
System in the development of public sector budgets have become multifunctional instruments that are used as a tool to achieve organizational goals. Budget is a plans of work that local government finances will be used as a basis for development in the region. In conducting the preparation, discussion, determination to supervise the implementation of the budget is not enough to just look at the size of the budget but also must the output produced by economically, efficiently and effectively for the betterment of the region. In this study, the authors want to analyze the performance of Sumenep goverment by using the principle of value for money which is based on three ratios is economical ratio, the efficiency ratio and effectiveness ratios. The results showed that the performance of Sumenep governments period 2010-2013 as a whole is goodKeyword : Value for money, economic, efficient, and effective